2017
DOI: 10.1111/ina.12433
|View full text |Cite
|
Sign up to set email alerts
|

Exposure reductions associated with introduction of solar lamps to kerosene lamp-using households in Busia County, Kenya

Abstract: Solar lamps are a clean and potentially cost-effective alternative to polluting kerosene lamps used by millions of families in developing countries. By how much solar lamps actually reduce exposure to pollutants, however, has not been examined. Twenty households using mainly kerosene for lighting were enrolled through a secondary school in Busia County, Kenya. Personal PM and CO concentrations were measured on a school pupil and an adult in each household, before and after provision of 3 solar lamps. PM concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…On the other hand, ambulatory CO levels among a cohort in urban Burkina Faso were about twice as high as those measured in our study [13], which may be related to the largely rural location of the participants in our cohort, though investigators identified a similar relationship between ambulatory CO levels and biomass smoke exposure. Ambulatory CO exposure was slightly higher among a rural Kenyan cohort of predominantly women who cooked mostly with firewood [45], which is likely due to the largely female composition of the Kenyan cohort, as meal preparation in East Africa is almost exclusively a woman’s responsibility. Lastly, while investigators from the AIR study in urban Malawi also measured personal CO levels in a case-control study of hospitalized patients with pneumonia [46], summative CO levels were not presented and authors did not investigate correlates of CO exposure, which limits comparisons with our work.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ambulatory CO levels among a cohort in urban Burkina Faso were about twice as high as those measured in our study [13], which may be related to the largely rural location of the participants in our cohort, though investigators identified a similar relationship between ambulatory CO levels and biomass smoke exposure. Ambulatory CO exposure was slightly higher among a rural Kenyan cohort of predominantly women who cooked mostly with firewood [45], which is likely due to the largely female composition of the Kenyan cohort, as meal preparation in East Africa is almost exclusively a woman’s responsibility. Lastly, while investigators from the AIR study in urban Malawi also measured personal CO levels in a case-control study of hospitalized patients with pneumonia [46], summative CO levels were not presented and authors did not investigate correlates of CO exposure, which limits comparisons with our work.…”
Section: Discussionmentioning
confidence: 99%
“…Very small quantities of kerosene can be lethal when ingested and kerosene looks like water and, in some countries, is often stored in soft drink bottles, which can easily be reached by children . Furthermore, “some studies suggest that kerosene is associated with health effects comparable with those of biomass burning for cooking, although a wider evidence base is needed to firmly establish this” (Lam et al, , p. 7).…”
Section: Differentiated Impact According To the Size Of The Systemsmentioning
confidence: 99%
“…Kerosene is similar to diesel fuel as a petroleum distillate, and therefore exposures of children and adults crowded around such lamps at night in a poorly ventilated home can be quite high. 11 In particular, there is evidence for increased risk of tuberculosis with household use of kerosene. 12…”
mentioning
confidence: 99%